Concrete quality assessment before building structures submitting to environmental exposure conditions - Castañeda, Abel; Howland Albear, Juan José; Corvo, Francisco; Marrero, Rigoberto (Revista de la Construcción. Journal of Construction, 2017)
A study on concrete quality assessment before building structures submitting to environmental exposure conditions was carried out. It was necessary to determine the ultrasonic velocity pulse, compressive strength and percentage of effective capillary porosity values in concretes probes of water/cement ratio 0.4, 0.5 and 0.6.The results allowed to demonstrate how from relationship between compressive strength and percentage of effective capillary porosity, as well as, from relationship between capillary coefficient absorption and percentage of effective capillary porosity, durability requirements were obtained. Durability requirements were: Critical value of percentage of effective capillary porosity from which the concrete permeability increased. Critical value of percentage of effective capillary porosity from which, compressive strength decreased. Ultrasonic pulse velocity and compressive strength tests by itself were not enough to concrete quality assessment. Results using the visual observation were confirmed, in the reinforced concrete probes exposed to corrosivity categories of the atmospheres very high (C5) and extreme (CX) in a tropical coastal climates during three years, as well as by scanning electron microscopy tests in small samples of hardened cement paste for the three water/cement ratios.